Credit Risk, Market Risk, Operational Risk and Liquidity Risk on Profitability of Banks in Indonesia - Muhammad Fahrul; Ellen Rusliati (Faculty of Economics and Business, University of Pasundan, 2016)
This study examines the effect of credit risk, market risk, operational risk, and liquidity risk on profitability of banks listed on the Indonesia Stock Exchange in 2010-2014. The method used is descriptive and verification methods, with a sample of 30 banks and using multiple regression analysis. The results showed that credit risk does not partially affect profitability. Market risk, operational risk, and liquidity risk partially have positive effect on profitability. It simultaneously shows that credit risk, market risk, operational risk and liquidity risk have effect on the profitability of banks amounted to 67.1%. Improvement of Non-Performing Loan, Net Interest Margin, Operating Expenses to Operating Income Ratio, and Loan to Deposit Ratio will increase the Profitability.